CSF and plasma testosterone in attempted suicide. (December 2016) - Stefansson, Jon; Chatzittofis, Andreas; Nordström, Peter; Arver, Stefan; Åsberg, Marie; Jokinen, Jussi
Highlights: CSF testosterone levels were higher in young male suicide attempters compared to age-matched healthy male volunteers. CSF testosterone/cortisol ratio showed a significant positive correlation with impulsivity and aggressiveness in male suicide attempters. CSF and plasma testosterone levels did not differ in female suicide attempters and healthy women. Abstract: Very few studies have assessed testosterone levels in the cerebrospinal fluid in suicide attempters. Aggressiveness and impulsivity are common behavioural traits in suicide attempters. Dual-hormone serotonergic theory on human impulsive aggression implies high testosterone/cortisol ratio acting on the amygdala and low serotonin in the prefrontal cortex. Our aim was to examine the CSF and plasma testosterone levels in suicide attempters and in healthy volunteers. We also assessed the relationship between the testosterone/cortisol ratio, aggressiveness and impulsivity in suicide attempters. 28 medication-free suicide attempters and 19 healthy volunteers participated in the study. CSF and plasma testosterone sulfate and cortisol levels were assessed with specific radio-immunoassays. The Karolinska Scales of Personality was used to assess impulsivity and aggressiveness. All patients were followed up for cause of death. The mean follow-up period was 21 years. Male suicide attempters had higher CSF and plasma testosterone levels than age- matched male healthy volunteers. There were no significant differences in CSF testosterone levels in female suicide attempters and healthy female volunteers. Testosterone levels did not differ significantly in suicide victims compared to survivors. In male suicide attempters, the CSF testosterone/cortisol ratio showed a significant positive correlation with both impulsivity and aggressiveness. Higher CSF testosterone levels may be associated with attempted suicide in young men through association with both aggressiveness and impulsivity, a key endophenotype in young male suicide attempters.